Spatial Planning of Marine Aquaculture Under Climate Decadal Variability: A Case Study for Mussel Farms in Southern California - Sainz, Jade F.; Di Lorenzo, Emanuele; Bell, Tom W.; Gaines, Steve; Lenihan, Hunter; Miller, Robert J. (Frontiers in Marine Science, 2019)
The growth of marine aquaculture over the 21st century is a promising venture for food security because of its potential to fulfill the seafood deficit in the future. However, to maximize the use of marine space and its resources, the spatial planning of marine aquaculture needs to consider the regimes of climate variability in the oceanic environment, which are characterized by large-amplitude interannual to decadal fluctuations. It is common to see aquaculture spatial planning schemes that do not take variability into consideration. This assumption may be critical for management and for the expansion of marine aquaculture, because projects require investments of capital and need to be profitable to establish and thrive. We analyze the effect of climate variability on the profitability of hypothetical mussel aquaculture systems in the Southern California Bight. Using historical environmental data from 1981 to 2008, we combine mussel production and economics models at different sites along the coast to estimate the Net Present Value as an economic indicator of profitability. We find that productivity of the farms exhibits a strong coherent behavior with marketed decadal fluctuations that are connected to climate of the North Pacific Basin, in particular linked to the phases of the North Pacific Gyre Oscillation (NPGO). This decadal variability has a strong impact on profitability both temporally and spatially, and emerges because of the mussels’ dependence on multiple oceanic environmental variables. Depending on the trend of the decadal regimes in mussel productivity and the location of the farms, these climate fluctuations will affect cost recovery horizon and profitability for a given farm. These results suggest that climate variability should be taken into consideration by managers and investors on decision making to maximize profitability.